A Mini-Review of the Potential Health Impacts of Indoor Radiation Exposure in Companion Animals - Sotirios Maipas; Ioannis O. Vardiambasis; Christos D. Nikolopoulos; Nikolaos Kavantzas (Environmental Health Insights)
Poor indoor environmental quality is a major concern for both humans and companion animals—yet its impact on the latter is often overlooked. This mini review sheds light on indoor radiation sources that may affect the health of companion animals. Radon, primarily from the ground and possibly also from cat litter, naturally occurring radionuclides in feed, radiofrequency radiation from mobile and cordless phones, Wi-Fi networks, pet tracking devices, solar radiation, and various sources of extremely low frequency radiation are all common examples. Indoor radiation, an odorless and tasteless pollutant, may have the potential to negatively impact the health and well-being of companion animals, which are involuntarily exposed to this environmental health risk factor. Therefore, preventive and precautionary measures are necessary.